The Effect of the Performance of the Board of Commissioners and Directors on Company Profitability in the 2019-2021 Jakarta Islamic Index (JII) With Salary as a Moderating Variable - Dwiyanti, Susi; Damanuri, Aji; Maharani, Shinta (Journal of Islamic Economics (JoIE), 2023)
Introduction: During the pandemic, many companies experienced a decline in profitability. One of them is what happened to companies included in the Jakarta Islamic Index (JII). During the pandemic the performance of the board of commissioners and directors could have been more optimal while the number of salaries for the board of commissioners and directors remained even increased. This can be seen from the profitability of several companies that are members of the Jakarta Islamic Index (JII), which are still below the average standard. The profitability of several companies that are members of the Jakarta Islamic Index (JII) is experiencing an imbalance. This study aims to determine the effect of the board of commissioners and directors on the profitability of companies that are members of the Jakarta Islamic Index (JII) for 2019-2021 and salary as a moderating variable. Research Methods: This study uses a population of companies that are members of the Jakarta Islamic Index (JII) for 2019-2021, using a sample of 54 companies. The type of this research is quantitative research. Meanwhile, data collection techniques use documentation and observation of the annual reports of companies that are members of the Jakarta Islamic Index (JII) for 2019-2021. Data analysis used is moderation regression analysis, classic assumption test, hypothesis testing and coefficient of determination (R2). Result: the results of this study indicate that the boards of commissioner variables affect the profitability of companies that are members of the Jakarta Islamic Index (JII) for 2019- 2021. The Directors influence the profitability of companies that are members of the Jakarta Islamic Index (JII) for 2019-2021. Meanwhile, salaries significantly moderate the influence of the board of commissioners and directors on the profitability of companies that are members of the Jakarta Islamic Index (JII) for 2019-2021. Conclusion: The results of this study indicate that the board of commissioners variables affect the profitability of companies that are members of the Jakarta Islamic Index (JII) for 2019-2021.